Cross-Cultural Aspects of Familie Theme in Learning German as a Foreign Language for Grade XI of Senior High School - Nastiti, Hadijah; Rosyidah, Rosyidah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This research aims to describe the cross-cultural aspects of the Familie theme in learning German and its implementation in learning German for XI grade of Senior High School. This research method used literature review: German curriculum for high school, syllabus, lesson plans, German language textbooks for A1 level high school, books, research results, and articles related to the use of intercultural learning methods. Then, all research data are grouped in tabular form, summarized and narrated. The results showed that the cross-cultural aspects studied in learning German for  XI gradecontained in Familie theme consisted of the sub-themes Familienaktivitäten, Familienstammbaum, Familienalbum, and Familienname. Cross-cultural aspects could be implemented in learning German in  XI grade Senior High School with three methods, they are discussion method, the comparing and commenting method, and the Stationenlernen method. Among the three methods, comparing and commenting methods are recommended to be implemented in learning German in XI grade of Senior High School.